EDUKASI KESELAMATAN LALU LINTAS DI KALANGAN EMAK-EMAK RW 02 DESA SOGO KABUPATEN BLORA - Magfirona, Alfia; Fitrianingrum, Wahyu Ria; Rahmawati, Febriria; Hidayati, Nurul; Sunarjono, Sri; Listyawan, Anto Budi; Handayani, Nur Khotimah (Abdi Masya, 2024)
The public's lack of awareness of traffic laws can be seen in behavior such as the increasing number of traffic violations. Apart from that, minimal knowledge of traffic rules and poor driving practices are also causes that exacerbate the high rate of traffic accidents. The rate of traffic accidents 2021 in Blora Regency throughout 2021 has increased compared to 2020. One effort to overcome this problem can be made by educating traffic ethics among the mothers of Sogo Village, Blora Regency. Service activities were carried out on Thursday, April 27 2023 at 15.00 – 17.00 WIB using the face-to-face method. The education carried out has been able to improve mothers' abilities to understand traffic and driving etiquette. Evaluation of service activities is carried out through pre-and post-tests. Based on the indicators per question item, the average pre-test results show a figure of 69.35%, while the post-test results have increased by 30.65%. Overall the results of the post-test percentage achieved per question item reached 100%. It can be concluded that the education carried out has succeeded in improving mothers' abilities to understand traffic and driving etiquette. In this way, these mothers are considered capable of sharing information and understanding related to traffic etiquette with their children and neighbors and can apply it in their behavior during traffic on the road as a follow-up to this activity.